Assessment of Nutritional Status of Guava Seedlings using Preliminary DRIS Norms and Sufficiency Ranges - Souza, H. A.; Rozane, D. E. [UNESP]; Amorim, D. A.; Dias, M. J. T. [UNESP]; Modesto, V. C. [UNESP]; Natale, W. [UNESP] (Taylor & Francis Inc, 2015)
The objective of this work was to propose preliminary Diagnosis and Recommendation Integrated System (DRIS) norms and derive critical levels and nutrient sufficiency ranges in the leaves of guava plants in commercial nursery conditions. Sixty-eight leaf samples were evaluated from fertilization trials with seedlings. In the low-yield subpopulation (84% of the population), the limiting nutrients by deficiency in descending order were nitrogen (N)> copper (Cu)>phosphorus (P) = potassium (K)> manganese (Mn)> iron (Fe) = zinc (Zn)> sulfur (S)> boron (B) = magnesium (Mg)> calcium (Ca), and the limiting ones by excess in descending order were B > Ca > Fe > Mn > S > Mg > Cu > P > Zn > N = K. The ranges of the appropriate DRIS indices were 24 to 28, 2.4 to 3.1, 21 to 29, 6 to 8, 1.9 to 2.9 and 1.9 to 2.3 (g kg(-1)) for the macronutrients N, P, K, Ca, Mg and S, respectively, and 35 to 48, 4 to 15, 68 to 93, 31 to 60 and 180 to 245 (mg kg(-1)) for the micronutrients B, Cu, Fe, Mn and Zn, respectively. The dry matter production of guava seedlings was associated with the nutritional status.
Keywords: Psidium guajava; leaf analysis; nursery